Generalized Darwinism in evolutionary economics: the devil is in the details - Jack Vromen (Max Planck Institute of Economics, 2007)
Hodgson and Knudsen want their version of Generalized Darwinism to meet two /desiderata. /First, their formulation of Darwinism should be sufficiently general and abstract, so that it only refers to general, domain-unspecific features that processes of biological and of socio-cultural evolution have in common with each other. Their formulation should leave out features of Darwinism that are specific to the biological domain only. Second, their version should be able to guide the development of theories that can causally explain processes of economic evolution. Hodgson and Knudsen argue that the latter - going from their abstract and general formulation of Darwinism to such full-fledged economic theories - is a matter of adding details that are specific to the economic domain. Both desiderata seem reasonable. Yet they pull in opposite directions. It is argued that in order to meet the first desideratum the formulation of Darwinism should be so general and abstract that it is bereft of any substance and content and, as such, of little use in guiding further theory development. If going from such a formulation to a full-fledged economic theory is called a matter of adding details, the devil surely is in the details.
Keywords: 330; Bioökonomik; Evolutionsökonomik; Theorie